Castle fear - Dixon, Franklin (,Simon and Schuster London, 1992)
The Hardy brothers are back for further adventures in this story. The brothers go to the rescue of a young American movie star, on location in England when they are soon drawn into a case worthy of Sherlock Holmes - and into a conspiracy as thick as the London fog.